Molecular and Morphological Evidence for the Description of Three Novel Velvet Worm Species (Onychophora: Peripatopsidae: Peripatopsis sedgwicki s.s.) from South Africa - Aaron Barnes; Savel R. Daniels (Diversity)
During the present study, DNA sequence and morphological data were used to delineate species boundaries in the velvet worm, Peripatopsis sedgwicki species complex. The combined mitochondrial cytochrome c oxidase subunit one (COI) and the nuclear 18S rRNA loci were phylogenetically analyzed using Bayesian inference and maximum likelihood platforms that both demonstrated the presence of four, statistically well-supported clades (A–D). In addition, five species delimitation methods (ASAP, bPTP, bGMYC, STACEY and iBPP) were used on the combined DNA sequence data to identify possible novel lineages. All five species delimitation methods supported the distinction of the Fort Fordyce Nature Reserve specimens in the Eastern Cape province, however, in the main P. sedgwicki s.l. species complex, the species delimitation methods revealed a variable number of novel operational taxonomic units. Gross morphological characters were of limited utility, with only the leg pair number in the Fort Fordyce Nature Reserve specimens and the white head-collar of the Van Stadens Wildflower Nature Reserve specimens being diagnostic. The RADseq results from the earlier study of P. sedgwicki s.l. provided highly congruent results with the four clades observed in the present study. The distribution of P. sedgwicki s.s. (clade B) is restricted to the western portions of its distribution in the Afrotemperate forested regions of the Western Cape Province, South Africa. Three novel species, P. collarium sp. nov., (clade C) P. margaritarius sp. nov., (clade A) and P. orientalis sp. nov., (clade D) are described, of which the first two species are narrow range endemics. The present study, along with several recent systematic studies of velvet worms affirms the importance of fine-scale sampling to detect and document the alpha taxonomic diversity of Onychophora.